Synthesis of AgNPs functionalized CuMOF/PPy–rGO nanocomposite and its use as an electrochemical sensor for metronidazole determination. Issue 10 (28th June 2021) - Saedi, Hamide; Fat'hi, Mohammad Reza; Zargar, Behrooz
Abstract: In this research, a simple and sensitive electrochemical technique based on using nanocomposite of (AgNP/CuMOF/PPy–rGO) modified carbon paste electrode for determination of metronidazole (MTZ) is described. Polypyrrole (PPy) hemispherical molecules coated reduced graphene oxide (PPy–rGO) was combined with CuMOF, a typical metal–organic framework, by hydrothermal method. AgNP/CuMOF/PPy–rGO was simply fabricated by creating AgNP inside and on the surface of the nanocomposite. The composition and morphology of the synthesized nanocomposite were investigated by SEM, FT‐IR, EDX, and XRD. Cyclic voltammetry and ASSWV were utilized to determine the electrocatalytic activity of the sensor regarding the reduction of MTZ. Interestingly, some outstanding properties of the nanocomposite including high surface area of CuMOF, good conductivity of PPy–rGO, and the catalytic activity of AgNPs could result in the enhancement of the electron transfer rate, electrochemical behavior, and the reduction of peak currents at the surface of the proposed sensor. Sensitive, promising, and stable electrochemical sensor exhibited linear detection range of 0.08–160 μM at pH 5.0 with detection and limit of 24 nM (S/N = 3). The system was validated for precision with standard deviation less than 2.0%. Moreover, its feasibility was successfully assessed through analysis of tablet and human urine. Abstract : Schematic illustration synthesis of AgNP/CuMOF/PPy–rGO nanocomposite. rGO was synthesized using thermal reduction of exfoliated graphene oxide nanosheet. Increased electrical conductivity of PPy/rGO due to the presence of PPy conductive polymer. Providing a new platform for decoration of MOFs over PPy/rGO. Eliminating the defect of MOFs by combining them with AgNPs. Using trisodium citrate as a stabilizing and reducing agent for preparation of AgNPs.